3D Lattice Structure Control of Ordered Macroporous Material by Self‐Assembly of Liquid Droplets. Issue 1 (24th October 2016) - Iwai, Yosuke; Uchida, Yoshiaki; Yabu, Hiroshi; Nishiyama, Norikazu
Abstract : Microfluidic devices, which can continuously fabricate single emulsion with monodispersed droplets having a pore diameter of more than 100 μm in large numbers, can be applied to manufacture ordered macroporous films. 3D ordered macroporous films with a diameter of more than 100 μm can be fabricated using ordered arrays of the monodispersed droplets as templates of the macropores, which are self‐assembled in the space between two parallel flat glass plates. As the gap between the glass plates increases, the number of the layer increases. Furthermore, in the case with two or more layers, the lattice structure of the macroporous films also changes due to the confinement effects. Abstract : 3D ordered macroporous films with a pore diameter of more than 100 μm can be fabricated using ordered arrays of monodispersed droplets self‐assembling in the space between two flat glass plates as templates. As the gap between the glass plates changes, the number of the layer and the lattice structure of the macroporous films change due to the confinement effects.